How Tesco used its clubcard programme to revive its brand and become a market leader - Stone, Merlin (Henry Stewart Talks, 2009)
Tesco's challenges in 1992, How Tesco achieved its growth, customer insights from the loyalty schemes, Tesco's pricing strategy